Relationship Knowledge and Profession of The Family and Mental Disorder in Municipality of Liquica, Timor-Leste - Maximiano Oqui; Alexandra Maria Pires; Eurico Amaral; Meriana Barreto Amaral; Áureo Frutalegio da Costa Freitas; Hermínio Noronha (Rifa'Institute, 2023)
Introduction: Mental health as an integral part of public and individual health, which is not free from mental disorders, but also has quality treatment for a healthy life. Mental health as an emotional, psychological condition and social relationship that can see interpersonal satisfaction, behavior, effective coping, positive concept, and emotional stability. Objective: The purpose of observing and doing a case study with the research process that submits this research, with the result want to know more in the scope of relating knowledge and family profession about giving care to the family member with a mental disorder. Method: This research uses the quantitative method and cross-sectional approach, which will be carried out in the Dato Village, Liquica Municipality, Timor-Leste. Result and Discussion: The result proves that it has stronger positive correlation than the value between 0.800 -1.000. Conclusion: knowledge result which has 68.8 % and family profession has 65.1 % with average knowledge and profession category which provide care for family member with mental disorder, Pearson Product Moment Test value proves that P-value 0.000, and R-value calculation 0.825**